Synthesis of hematite α-Fe2O3 nano powders by the controlled precipitation method / Síntesis de nano polvos de hematita α-Fe2O3 por el método de precipitación - MORALES MORALES, JIMMY ALEXANDER (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Increased attention has been paid to the synthesis of hematite nanoparticles recently due to its properties and application in various fields of modern technology. The aqueous route has been found to be simpler and more versatile than the non-aqueous routes. In this study nanopowder of a-Fe2O3 (hematite) were synthesized by controlled precipitation method in three stages: precipitation of precursors, washing and calcination. The precipitation was controlled with ferric chloride as precursor, and sodium hydroxide as precipitant, in constant agitation and pH 6. It tested different reaction times: 1 and 2 days, and after 2 day of reaction it was concluded that it is possible to obtain hematite. The products obtained from the reaction were washed by centrifugation, dried at 80 ◦C, and were calcined at temperature of 425 ◦C, for four hours. To characterize the product obtained in the synthesis, it has been used FT-IR, SEM and RAMAN techniques. Samples with two days of reaction, washed and calcination at 425 ◦C are associated a mixture of hematite and magnetite and maghemite, with nearly morphology from plate-like shaped sphere and aggregates are formed by hemispherical primary particles whose size, apparently, is on the order of nanometers.